2017
DOI: 10.21475/ajcs.17.11.02.p305
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation affecting latex physiology and yield under low frequency tapping of rubber (Hevea brasiliensis) clone RRIM 600 in southern Thailand

Abstract: Some of the authors of this publication are also working on these related projects:Land and labor productivity, good agricultural practices in rubber tree cultivation View project Metabolism and carbon allocation : Sink-source relationship at tree scale in relation with the latex Tapping and ethylene stimulation induces the dynamic change of latex cell metabolism. Those changes under the implement of low frequency tapping systems with ethylene stimulation were investigated during the both periods (low yield an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Interestingly, several studies showed a drop in RSH after long-term effect of high ethephon stimulation frequency (HSF) ( Lacote et al., 2010 ; Traore et al., 2011 ; Dian et al., 2016a ; Dian et al., 2017 ) and high tapping frequency (HTF) ( Obouayeba et al. 2009 ), although in other study was stable ( Sainoi et al., 2017a , Sainoi et al., 2017b ). In long-term observation, RSH was generally lower for high-stress treatment than lower stress counterpart and was accompanied by low Suc and Pi.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, several studies showed a drop in RSH after long-term effect of high ethephon stimulation frequency (HSF) ( Lacote et al., 2010 ; Traore et al., 2011 ; Dian et al., 2016a ; Dian et al., 2017 ) and high tapping frequency (HTF) ( Obouayeba et al. 2009 ), although in other study was stable ( Sainoi et al., 2017a , Sainoi et al., 2017b ). In long-term observation, RSH was generally lower for high-stress treatment than lower stress counterpart and was accompanied by low Suc and Pi.…”
Section: Discussionmentioning
confidence: 99%
“…For some rubber clones, tapping is combined with ethephon stimulation to increase latex yield. Several studies revealed that this combination modifies laticifer metabolic activities and latex flow ( Silpi et al., 2006 ; Wei et al., 2015 ; Sainoi et al., 2017a , Sainoi et al., 2017b ). However, over-tapping and over-stimulation lead to tapping panel dryness (TPD) occurrence, a physiological syndrome hampering latex flow ( Bealing and Chua, 1972 ; Senevirathna and Nugawela, 2009 ; Putranto et al., 2015 ; Samuel et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Hal ini dikarenakan tanaman saat pengamatan masih tergolong puncak produksi di wilayah Sumatera Utara yang umumnya terdapat pada Semester II. Hasil penelitian Sainoi et al, (2017) saat produksi rendah selama sembilan tahun dengan kondisi normal menyatakan bahwa rata-rata produksi 17,96 g/p/s tanpa stimulan dan 43,13 g/p/s dengan stimulan konsentrasi 2,5% pada kondisi tanaman tidak terserang penyakit gugur daun sekunder. Penelitian tersebut menandakan bahwa selama perdaunan normal, tanaman karet akan responsif terhadap stimulan dengan konsentrasi 2,5% dibandingkan tidak diaplikasikan stimulan etefon.…”
Section: Produksi Pada Tanaman Umur 8 Tahununclassified
“…The number of publications remained high after 2013, even reached a peak in 2015-2017 (Supplementary data 2). The experiments of low-frequency tapping accompanied by stimulation modification, for example, the works by Sainoi et al (2017), Atsin et al (2014), andPhearun et al (2019), contributed to a significant report on LD application. These typical studies might be a response to the low natural rubber price in order to reduce the tapping cost.…”
Section: Application Of Latex Diagnosis In Rubber Plantations and Res...mentioning
confidence: 99%